HUBUNGAN JENIS KELAMIN DAN POLA MAKAN DENGAN KEJADIAN DIABETES MELITUS TIPE 2 PADA USIA PRODUKTIF DI WILAYAH KERJA PUSKESMAS SERING MEDAN - Purba, Monalisa Lavenia; Wahyu, Afnijar (Excellent Midwifery Journal, 2025)
Background: WHO data states that 422 million people in the world suffer from Diabetes Mellitus or an increase of 8.5% in the population before the age of 65 (productive age). Factors that are thought to be associated with the incidence of type II diabetes mellitus in productive age are gender, genetic factors, body mass index, smoking history, physical activity, and eating patterns. Objective: To determine the risk factors associated with the incidence of type II diabetes mellitus in productive age. Methods: This research is a quantitative study using a cross-sectional survey approach. The research was conducted in the working area of the Sering Medan Health Center. Total population of 437 people and samples obtained as many as 82 people. Withdrawal of samples by purposive sampling. The data used are primary data and secondary data. The analysis was carried out univariately and bivariately by using Spearman's Rank test. Results: The risk factors associated with the incidence of type II diabetes mellitus in productive age in the working area of the Sering Medan Health Center is diet (p=0.000, r = 0.689). Meanwhile, the unrelated factor was gender (p=0.178). Conclusion: diet is associated with the incidence of type II diabetes mellitus in productive age. Suggestion: It is expected that health workers (nurses) will routinely provide health education to people of productive age who visit the puskesmas about the risk factors for type II diabetes mellitus.